(untitled) (Religious dialogue and cooperation, 2021)
The German Catholic monk Martin Luther (1483−1546), reformer and rebel, who created a schism in the Roman Catholic and Protestant/Evangelical churches, is also well known for his translation of the Bible from Hebrew (original: Old Testament) and Greek (original: New Testament) into German. In conflict with the then-head of the Roman Catholic Church, later even causing a dispute with the Pope and the Vatican because of its reform topics, he was guided by the premise that the Bible should be understood predominantly by the people, and not only by the clergy and the authorities. Luther’s idea results in a German Bible translation that departs from the sacral Hebrew, Greek, and also Latin (Vulgate) language dogmas moving toward a linguistic interpretation that “looks into the people’s mouths” (“Dem Volke aufs Maul schauen”). This kind of specific rendering leads Luther to break with tradition twice: firstly by using primarily the original linguistic codes and registers and secondly by breaking free from the sacramental function of the original Bible text by not translating literally (word-for-word), which was the case with previous German Bible translations. The paper highlights the fact that Luther’s rendering of the Bible united the Germans linguistically and laid the foundations for the so-called German unitary language. In addition, the paper discusses whether the popularization of the German language in the Bible establishes greater proximity to the believers and may be viewed as a popular or even populist instrument.